Multiple cutaneous and uterine leiomyomas: A case report - Thatte, Sharvil; Gupta, Brajesh; Dakhore, Sanjay; Diyewar, Ayush; Nayak, Vinod (Indian Journal of Case Reports, 2025)
Piloleiomyomas are uncommon benign papulo-nodular tumors arising from the erector pili muscle, often found with a segmental cutaneous distribution. While the presenting complaint for these patients may be intermittent pain in the swellings, they are associated with hereditary syndromes which, more importantly, require further surgical attention, namely Reed Syndrome (multiple cutaneous and uterine leiomyomatosis) and hereditary leiomyomatosis and renal cell carcinoma syndrome. We present a case of a 30-year-old woman who was referred to us for excision of multiple painful cutaneous lesions which were present over her left breast, who had a past history of primary infertility with multiple uterine fibroids requiring laparoscopic myomectomy 3 years back, with no significant family history. Few small lesions had been treated with cryotherapy before she was referred to us. The patient underwent excision under local anesthesia of the largest of the lesions causing the most pain and the histopathological examination determined it to be a piloleiomyoma. Abdominal ultrasonography revealed bilaterally normal kidneys with a small asymptomatic uterine fibroid. Post excision, the patient was pain-free and no surgical site recurrences were observed on follow-up after 1 year.